A Case of Advanced Gastric Cancer with Para-Aortic Lymph Node Metastasis from Co-Occurring Prostate Cancer - Park, Miyeong (J Gastric Cancer, 2017)
An 84-year-old man was diagnosed with two synchronous adenocarcinomas, a Borrmann type IV advanced gastric adenocarcinoma in his antrum and a well-differentiated Borrmann type I carcinoma on the anterior wall of the higher body of his stomach. Pre-operatively, computed tomography of the abdomen revealed the presence of advanced gastric cancer with peri-gastric and para-aortic lymph node (LN) metastasis. He planned for palliative total gastrectomy owing to the risk of obstruction by the antral lesion. We performed a frozen biopsy of a para-aortic LN during surgery and found that the origin of the para-aortic LN metastasis was from undiagnosed prostate cancer. Thus, we performed radical total gastrectomy and D2 LN dissection. Post-operatively, his total prostate-specific antigen levels were high (227 ng/mL) and he was discharged 8 days after surgery without any complications.